2015
DOI: 10.1080/1068316x.2015.1008476
|View full text |Cite
|
Sign up to set email alerts
|

The role of moral disengagement in street gang offending

Abstract: Previous research indicates a strong association between gang membership and increased offending behaviour. Several risk factors for gang membership have been identified and incorporated into integrated and developmental theories of gang membership. Despite this, little is known about the psychological processes that underpin gang membership and enhance the rate of offending within this context. Even less is known of the differences in such psychological processes between gang offenders and those who offend in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
2
11
0
1
Order By: Relevance
“…Our findings that moral disengagement and rumination both predict gang involvement suggest that gang-involved youth ruminate on anger-provoking events, and probably adopt moral disengagement strategies to justify their rumination-elicited violence. These findings further support previous work such as that of Vasquez et al (2012), who also found that gang-affiliated youth were more likely to engage in rumination, and Niebieszczanski and colleagues (2015), who noted how street gang members, compared with non-gang youth, used moral disengagement strategies (e.g. attributing blame to others and employing reconstructive language, i.e.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings that moral disengagement and rumination both predict gang involvement suggest that gang-involved youth ruminate on anger-provoking events, and probably adopt moral disengagement strategies to justify their rumination-elicited violence. These findings further support previous work such as that of Vasquez et al (2012), who also found that gang-affiliated youth were more likely to engage in rumination, and Niebieszczanski and colleagues (2015), who noted how street gang members, compared with non-gang youth, used moral disengagement strategies (e.g. attributing blame to others and employing reconstructive language, i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Equally, research has shown that street gang members are more likely to morally disengage than are non-gang offenders by adopting a range of moral disengagement strategies, such as displacement of responsibility (e.g., to other gang members or to victims) and dehumanizing victims (Alleyne, Fernandes and Pritchard, 2014;Niebieszczanski et al, 2015). The more the individual benefits from the harmful behavior (e.g., positive reinforcement from other gang members for violence, which may boost self-esteem), the more morally disengaged the individual will become.…”
Section: Affective Behavioral and Socio-cognitive Processesmentioning
confidence: 99%
“…These mechanisms were first described by Bandura et al (1996) to explain the self-exonerative cognitive processes that people use when they violate moral norms. Previous research showed that civic moral disengagement behaviors are related to violence and aggression (e.g., Caprara, Tisak, Alessandri, Fontaine, Fida, & Paciello, 2014;Maftei et al, 2019), street gang offending (Niebieszczanski et al, 2015), driving violations (Holman & Popusoi, 2018), and generally, lower self-restraints related to antisocial behaviors (Fontaine et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Respecto a estos delitos graves contra las personas, ello es muestra de cómo en aquellas infracciones penales en las que existe una víctima directa se ha de realizar un mayor esfuerzo cognitivo/emocional para eliminar las barreras inhibitorias ya comentadas. Además, es muy probable que en muchos de los individuos de los estudios recopilados, la propia institucionalización haya contribuido en modo significativo al incremento y cronificación en el uso de los mecanismos de desconexión moral (Férriz et al, 2018;Niebieszczanski, Harkins, Judson, Smith & Dixon, 2015), generando trayectorias delictivas cronificadas.…”
Section: Discussionunclassified